PENGOLAHAN FOTO UDARA DRONE MENGGUNAKAN PERANGKAT LUNAK Pix4DMAPPER (Drone Aerial Photograph Processing Using Pix4D Mapper Software) - Arthur Gani Koto (Jurnal Sains Informasi Geografi (J SIG), 2021)
Abstract - A recording project using a drone where one of the results is in the form of aerial photographs, it is necessary to carry out further processing, namely a mosaic to obtain the final result in the form of an orthomosaic. It is intended that it can be analyzed for various interests, especially in the field of earth. This study aims to show how to process drone aerial photos into orthomosaic using a desktop PC that has Pix4Dmapper software installed. The data used is an aerial photo of the PRPM area "tracking mangrove in love" totaling 112 images recorded by the DJI Phantom 4 drone. The processing process used a PC desktop with specifications : AMD FX 8300 CPU, 16 GB DDR3 RAM, GPU: AMD Radeon (TM) R9 200 Series 2 GB, HDD: 1 TB 5400 rpm, and Windows 10 Enterprise 64-bit operating system. The method used is processing drone aerial photos into orthomosaic and DSM on the Pix4Dmapper software using a PC Desktop. During aerial photo processing, temperature observations (CPU, RAM, GPU, HDD, Motherboard) are also carried out using the CPUID HWMonitor application and observing hardware workloads (CPU, RAM, GPU, HDD) using the Task Manager application. Initial processing and DSM, Orthomosaic, and Index are performed by default setting. Point Cloud and Mesh settings for image scale: slow and point density: high, otherwise they are the default. The results showed that the need for processing drone aerial photos into orthomosaic and DSM can be done with the desktop PC specifications mentioned above. The total time required during the processing process is 5 hours 18 minutes 28 seconds.Keywords: aerial photograph, drone, orthomosaic, pix4d mapper   Abstrak – Kegiatan perekaman menggunakan drone yang salah satu hasilnya berupa foto udara perlu dilakukan pengolahan lebih lanjut yaitu mosaik agar diperoleh hasil akhir berupa orthomosaic. Hal ini bertujuan agar dapat dianalisis untuk berbagai kepentingan khususnya dibidang kebumian. Penelitian ini bertujuan untuk menunjukkan bagaimana pengolahan foto udara drone menjadi orthomosaic menggunakan PC Desktop yang telah terinstall perangkat lunak Pix4Dmapper. Data yang yang digunakan yaitu foto udara kawasan PRPM “tracking mangrove in love” berjumlah 112 image yang direkam drone DJI Phantom 4. Proses pengolahan menggunakan PC desktop dengan spesifikasi CPU AMD FX 8300, 16 GB RAM DDR3, GPU: AMD Radeon (TM) R9 200 Series 2 GB, HDD: 1 TB 5400 rpm, dan sistem operasi Windows 10 Enterprise 64-bit. Metode yang digunakan yaitu pengolahan foto udara drone menjadi orthomosaic dan DSM pada perangkat lunak Pix4Dmapper menggunakan PC Desktop. Selama pengolahan foto udara berlangsung, dilakukan pula pengamatan suhu (CPU, RAM, GPU, HDD, Motherboard) menggunakan aplikasi CPUID HWMonitor dan pengamatan beban kerja  perangkat keras (CPU, RAM, GPU, HDD) menggunakan aplikasi Task Manager. Pengaturan Initial processing dan DSM, Orthomosaic, and Index dilakukan secara default. Pengaturan Point Cloud and Mesh untuk image scale : slow dan point density : high, selain itu default. Hasil penelitian menunjukkan bahwa kebutuhan untuk pengolahan foto udara drone menjadi orthomosaic dan DSM dapat dilakukan dengan spesifikasi PC Desktop tersebut diatas. Total waktu yang dibutuhkan selama proses pengolahan yaitu 5 jam 18 menit 28 detik.Kata kunci: foto udara, drone, ortomosaic, pix4d mapper